Optimization of Auction Execution in Dispute Resolution in Class IA Baturaja Religious Court - Weri Edwardo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Basically in inheritance and joint property disputes, the reason for resolving disputes through auctions is because one of the parties does not carry out the decision voluntarily. In addition, in sharia economic disputes there are 3 (three) things that form the basis of auction implementation, namely parties breaking promises (defaults), unlawful acts, and due to coercive circumstances. The purpose of carrying out dispute resolution is to create a law that contains the value of legal justice, the value of legal certainty, and the value of legal benefits. Settlement of disputes through an auction procedure in the Religious Courts is an effort to create legal certainty for justice seekers. This study aims to provide information regarding dispute resolution procedures through auction procedures at the Religious Courts.This research was conducted using the normative-empirical juridical research method, which combines normative legal approaches with the addition of various empirical elements. The results of this study are that in carrying out auction execution, various obstacles are often encountered, one of which is resistance from the executed party or third parties. Apart from that, the condition of the Covid-19 Pandemic also presented obstacles to the process and the determination of the execution schedule. These two obstacles also cause the execution processCase No2/Pdt.Ex/2021/PA. Bta didn't go well.